2022
DOI: 10.1080/2090598x.2021.2024984
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer in the Arab world: Bibliometric review and research priority recommendations

Abstract: Objective To conduct a scoping review examining the status of prostate cancer research in Arab countries and systematically map publications across the cancer care pathway. Prostate cancer incidence has been rising in the Arab world and tackling its increasing burden will require evidence-based policies. Methods We searched Medline, PubMed and Scopus for peer-reviewed publications related to both our research topic and countries of interest by using controlled vocabular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Notably, the UCR's participation rate in international cancer research publications is 0.06%, compared to 1.52% for all Arab nations combined [ 2 ]. The results of the current study are consistent with previous bibliometric studies on cancer in the Arab world [ 40 , 41 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Notably, the UCR's participation rate in international cancer research publications is 0.06%, compared to 1.52% for all Arab nations combined [ 2 ]. The results of the current study are consistent with previous bibliometric studies on cancer in the Arab world [ 40 , 41 ].…”
Section: Discussionsupporting
confidence: 92%
“…Despite ongoing monitoring and early detection efforts, the incidence and mortality rates of diagnosed cancer in the UAE have been steadily increasing, highlighting the need for improved coverage within the population [ 6 ]. This study employed bibliometric analysis to examine the historical trends in UAE cancer research (UCR), a technique previously used to map cancer research landscapes in various regions [ 2 , [37] , [38] , [39] ] including Arabic countries [ 40 ]. We investigated the cancer-related scholarly output of UAE university scholars, encompassing not only clinical trials, but also observational and epidemiological studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the incidence of prostate cancer is increasing, data on the stage at diagnosis and treatment outcomes remain scarce, potentially leading to increased mortality rates. Concurrently, lower incidence rates might be attributed to biological features of male populations in the Arab World, as suggested by several studies 5,19,20 . Access to health care, an important determinant of cancer outcomes, is unfortunately limited or negatively impacted by conflict and displacement in many parts of the Middle East, 21–23 which could result in delayed diagnosis and consequently, higher mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a geographically and temporally limited study highlighted that cancer research productivity in Arab countries is lower than in the United States (US), Europe, and Japan, mainly due to the limited number of researchers, and lack of funding, networking, and research support (11). A recent study examining the status of prostate cancer research in the Arab world identified a positive correlation between the GDP and research output, a focus on diagnosis and treatment rather than screening and prevention, and a lack of research funded or co-authored by women (12). To holistically understand the evolution of research productivity on cancer in the Arab world, such studies should be expanded to other types and categories within the field of oncology, including genitourinary (GU) cancers.…”
Section: Introductionmentioning
confidence: 99%